Microneedle-Based Device for Biological Analysis - Lu, Huiting; Zada, Shah; Yang, Lingzhi; Dong, Haifeng (Frontiers in Bioengineering and Biotechnology, 2022)
The collection and analysis of biological samples is an effective means of disease diagnosis and treatment. Blood sampling is a traditional approach in biological analysis. However, this approach is inextricably associated with invasive techniques, and blood sampling is usually performed by a professional. The microneedles (MNs)-based devices has gained increasing attention due to its non-invasive manner compared traditional blood-based analysis method. In present review we introduce the materials for fabrication of MNs. We categorize MNs-based device based on four classes: MNs for transdermal sampling, biomarker capture, detection or monitoring analytes, and bio-signal recording. The design strategies and corresponding application of them are highlight and discussed in detail. Finally, future perspectives of MNs-based device are discussed.